Petrogenesis of Middle Silurian Shandan diorites in North Qilian Orogenic Belt, NW China: Insights into post-collisional slab breakoff - Chen, Gang; Li, Dechao; Liu, Xijun; Liu, Pengde; Bai, Zhihan; Liu, Xiao; Hu, Rongguo; Tian, Hao; Liu, Yande; Huang, Wenmin; Xiao, Yao (Frontiers in Earth Science, 2025)
Paleozoic intrusive rocks are exposed in the Longshoushan area in NW China, in the Northern Qilian Block and on the southern edge of the Alxa Block. Understanding the petrogenesis and tectonic setting of these intrusive rocks is crucial for reconstructing the tectonic evolution and tectonomagmatic processes that occurred along the North Qilian Orogenic Belt between the Alxa and Central Qilian blocks. This study presents an integrated analysis of petrology, zircon U-Pb geochronology, whole-rock geochemistry, along with Sr–Nd–Pb isotopic data and zircon Hf–O isotopic analyses for these intrusive rocks. The Shandan intrusive rocks consist primarily of calc-alkaline quartz diorite (∼430 Ma) and diorite (∼403 Ma). These diorites are enriched in large-ion lithophile elements (e.g., Ba and U) and depleted in high field strength elements (e.g., Nb, Ta, and Ti), similar to subduction-related magmas. The Shandan diorites have enriched Sr and Nd isotopic compositions, with high initial 87Sr/86Sr ratios (0.705247–0.70618), variable εNd(t) values (−1.58 to −3.53), positive zircon εHf(t) values (+0.08 to +3.55) and low zircon δ18O values (5.75‰–6.38‰). The older zircon grains (430 Ma) yield εHf(t) values of +0.14 to +6.58 and the younger grains (403 Ma) yield negative εHf(t) values (+2.24 to −11.0). The geochemical and isotopic data suggest that the diorites were derived through low-degree partial melting of enriched subcontinental lithospheric mantle with the addition of crustal material and subduction-related sediment-derived melts. We suggest that the formation of the Shandan diorites was dominated by slab breakoff at ∼430 Ma, which created a window that enabled the upwelling of asthenospheric material and induced partial melting of the subcontinental lithospheric mantle and crust. At ∼403 Ma, slab breakoff was nearing end, leading to weaker asthenospheric upwelling.